2008
DOI: 10.1021/cg800163f
|View full text |Cite
|
Sign up to set email alerts
|

Growth Optimization and Optical Characteristics of Fe Doped LiNbO3 Crystals

Abstract: Fe doped lithium niobate, LiNbO3 (LN), crystals were grown successfully by the Czochralski technique. Growth parameters were optimized to get a constant diameter crystal without using the automatic diameter control (ADC) system. A broad absorption band centered at 488 nm has been observed in the absorption studies due to 2eg and 2t2g transition. The significant red shift in UV absorption edges indicates a decrease in the Li/Nb ratio in the Fe doped LiNbO3 crystals. Energy dispersive analysis by X-ray (EDAX) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…7(c) depicts that the optical band gap is reduced to 3.49 eV as compared to that of reported $3.9 eV for pure LN crystals. 57 The transparency with sharp absorption at 482 nm of grown crystal is much higher as compared to the earlier reported LN crystal 58 with much lower iron concentration ($0.028 mol%). Therefore, the Fe : LN crystal grown in the present study seems to be very good for the optical information processing 59 and holographic data storage applications.…”
Section: Uv-vis Analysismentioning
confidence: 62%
“…7(c) depicts that the optical band gap is reduced to 3.49 eV as compared to that of reported $3.9 eV for pure LN crystals. 57 The transparency with sharp absorption at 482 nm of grown crystal is much higher as compared to the earlier reported LN crystal 58 with much lower iron concentration ($0.028 mol%). Therefore, the Fe : LN crystal grown in the present study seems to be very good for the optical information processing 59 and holographic data storage applications.…”
Section: Uv-vis Analysismentioning
confidence: 62%
“…These crystalline defect centres intern reflects in the form of optical inhomogeneity in the crystals at microscopic level. Recently it has been found that the birefringence interferometry is very attractive and precise technique to investigate the optical homogeneity in NLO crystals [17]. Well-ground and polished Mn: Li 2 B 4 O 7 crystal element was studied for optical homogeneity using birefringence interferometry.…”
Section: Methodsmentioning
confidence: 99%
“…This further extends the use of birefringence in obtaining seeds for directional growth along the optic axis. Comparisons of birefringence value of some other crystals (Kar et al 2008(Kar et al , 2009) are given in table 2.…”
Section: Birefringence Measurementsmentioning
confidence: 99%